Prevalensi dan Faktor Penentu Gangguan Emosional Pasca Persalinan Dini pada Ibu Setelah Operasi Caesar: Tinjauan Sistematis - Ernawati Ernawati; Wahyuni Hafid; Fony Fony; Rismanudin Rismanudin; Dewi Safitri; Sukmawati Anwar (An Idea Health Journal, 2025)
Early postpartum emotional disturbance remains an important maternal health concern following cesarean section because postoperative pain, delayed physical recovery, and childbirth-related psychological stress may increase maternal emotional vulnerability during the puerperium. If not recognized early, these emotional disturbances may interfere with breastfeeding adaptation, infant care, maternal well-being, and mother–infant bonding. This systematic review aimed to identify the prevalence and dominant determinants of early postpartum emotional disturbance among mothers after cesarean section. A systematic literature search was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using PubMed, Scopus, ScienceDirect, and Google Scholar for peer-reviewed articles published between 2016 and 2026. After title screening, abstract screening, and full-text eligibility assessment, 33 studies were included in the final synthesis. The reviewed evidence demonstrated that emotional disturbances during the early postpartum period among mothers after cesarean section were consistently reported across different populations. Psychosocial determinants, particularly antenatal anxiety, previous emotional vulnerability, maternal stress, and inadequate husband or family support, emerged as the most dominant contributing factors. Clinical contributors such as emergency cesarean procedures, postoperative pain, sleep disturbance, hormonal fluctuation, and delayed postoperative recovery further intensified maternal emotional instability. The findings indicate that postpartum care after cesarean section should integrate early psychological screening, effective postoperative symptom management, and family-centered emotional support to reduce the risk of persistent maternal psychological disorders.